Advances in Human Factors and System Interactions Proceedings of the AHFE 2016 International Conference on Human Factors and System Interactions, July 27-31, 2016, Walt Disney World®, Florida, USA - Nunes, Isabel L. (Advances in Intelligent Systems and Computing, 2017)
This book reports on cutting-edge research in innovative systems interfaces, with an emphasis on both lifecycle development and human-technology interaction, especially in the cases of virtual, augmented and mixed reality systems. It describes advanced methodologies and tools for evaluating and improving interface usability and covers new models, as well as case studies and good practices. The book reports on considerations of the human, hardware, and software factors in the process of developing interfaces for optimizing total system performance, especially innovative computing technologies for teams dealing with dynamic environments, while minimizing total ownership costs. One of the main purposes is to discuss forces currently shaping the nature of computing and systems including: the needs of decreasing hardware costs; the importance of portability, which translates to the modern tendency of hardware miniaturization and technologies for reducing power requirements; the necessityof a better assimilation of computation in the environment; and social concerns about access to computers and systems for people with special needs. The book, which is based on the AHFE 2016 International Conference on Human Factors and System Interactions, held on July 27-31, 2016, in Walt Disney World®, Florida, USA, offers a timely survey and practice-oriented guide for systems interface users and developers alike. .